Erv14 cargo receptor participates in regulation of plasma-membrane potential, intracellular pH and potassium homeostasis via its interaction with K+-specific transporters Trk1 and Tok1 - Zimmermannová, Olga; Felcmanová, Kristina; Rosas-Santiago, Paul; Papoušková, Klára; Pantoja, Omar; Sychrová, Hana (Biochimica et biophysica acta. Molecular cell research, 2019)
Cargo receptors in the endoplasmic reticulum (ER) recognize and help membrane and soluble proteins along the secretory pathway to reach their location and functional site. We characterized physiological properties of Saccharomyces cerevisiae strains lacking the ERV14 gene, which encodes a cargo receptor part of COPII-coated vesicles that cycles between the ER and Golgi membranes. The lack of Erv14 resulted in larger cell volume, plasma-membrane hyperpolarization, and intracellular pH decrease. Cells lacking ERV14 exhibited increased sensitivity to toxic cationic drugs and decreased ability to grow on low K+. We found no change in the localization of plasma membrane H+-ATPase Pma1, Na+, K+-ATPase Ena1 and K+ importer Trk2 or vacuolar K+-Cl- co-transporter Vhc1 in the absence of Erv14. However, Erv14 influenced the targeting of two K+-specific plasma-membrane transport systems, Tok1 (K+ channel) and Trk1 (K+ importer), that were retained in the ER in erv14Δ cells. The lack of Erv14 resulted in growth phenotypes related to a diminished amount of Trk1 and Tok1 proteins. We confirmed that Rb+ whole-cell uptake via Trk1 is not efficient in cells lacking Erv14. ScErv14 helped to target Trk1 homologues from other yeast species to the S. cerevisiae plasma membrane. The direct interaction between Erv14 and Tok1 or Trk1 was confirmed by co-immunoprecipitation and by a mating-based Split Ubiquitin System. In summary, our results identify Tok1 and Trk1 to be new cargoes for Erv14 and show this receptor to be an important player participating in the maintenance of several physiological parameters of yeast cells.
Keywords: Saccharomyces cerevisiae; biologický transport; regulace genové exprese u hub; membránové potenciály; glukosa; membránové proteiny; Glucose; Potassium; Endoplasmic Reticulum; Membrane Proteins; endoplazmatické retikulum; Gene Deletion; draslík; Cell Membrane; koncentrace vodíkových iontů; Golgiho aparát; transkriptom; Biological Transport; Cation Transport Proteins; Saccharomyces cerevisiae Proteins; Saccharomyces cerevisiae - proteiny; sodíko-draslíková ATPasa; Membrane Potentials; Cell Size; Proton-Translocating ATPases; Transcriptome; velikost buňky; delece genu; Hydrogen-Ion Concentration; homeostáza; Potassium Channels; protonové ATPasy; draslíkové kanály; buněčná membrána; sodík; proteiny přenášející kationty; COP-vezikuly; Gene Expression Regulation, Fungal; Sodium-Potassium-Exchanging ATPase; Homeostasis; Sodium; COP-Coated Vesicles; Golgi Apparatus